Penalized Splines, Mixed Models and the Wiener-Kolmogorov Filter - Andreas Bloechl (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
Penalized splines are widespread tools for the estimation of trend and cycle, since they allow a data driven estimation of the penalization parameter by the incorporation into a linear mixed model. Based on the equivalence of penalized splines and the Hodrick-Prescott filter, this paper connects the mixed model framework of penalized splines to the Wiener- Kolmogorov filter. In the case that trend and cycle are described by ARIMA-processes, this filter yields the mean squarred error minimizing estimations of both components. It is shown that for certain settings of the parameters, a penalized spline within the mixed model framework is equal to the Wiener-Kolmogorov filter for a second fold integrated random walk as the trend and a stationary ARMA-process as the cyclical component.
urn:nbn:de:bvb:19-epub-21406-9
Keywords: C22; C52; 330; Hodrick-Prescott filter; mixed models; penalized splines; trend estimation; Wiener-Kolmogorov filter